2021
DOI: 10.1016/j.cub.2021.08.016
|View full text |Cite
|
Sign up to set email alerts
|

Energy compensation and adiposity in humans

Abstract: Highlights d Energy compensation in humans was analyzed from daily and basal energy expenditure d Reduced BEE results in energy compensation of 28% d Degree of energy compensation varied between people of different body composition

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
62
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(69 citation statements)
references
References 40 publications
3
62
0
4
Order By: Relevance
“…Weight-loss therapies have been largely unsuccessful due to low adherence and unwanted side effects ( 70 ). Weight-loss strategies may be less effective in obese individuals due to compensations in energy expenditure resulting from caloric restriction or exercise ( 71 , 72 ). Increasing energy expenditure via β3 agonists has been explored clinically and has shown some positive results in healthy and obese humans ( 58 , 73 76 ).…”
Section: Discussionmentioning
confidence: 99%
“…Weight-loss therapies have been largely unsuccessful due to low adherence and unwanted side effects ( 70 ). Weight-loss strategies may be less effective in obese individuals due to compensations in energy expenditure resulting from caloric restriction or exercise ( 71 , 72 ). Increasing energy expenditure via β3 agonists has been explored clinically and has shown some positive results in healthy and obese humans ( 58 , 73 76 ).…”
Section: Discussionmentioning
confidence: 99%
“…A greater NetC w/kg therefore represents a potential target for morbid obesity management through the daily total energy expenditure increase (TEE), especially in sedentary people with obesity who are in the so-called "unregulated zone", in which appetite and food intake are not affected by TEE; thus, food intake drives body weight gain [44]. Although increasing physical activity using walking and its associated higher NetC w/kg could be useful to shift individuals with obesity into the "regulated zone", in which appetite and food intake are affected by physical activity [44], the role of the latter in energy balance and weight loss remains controversial [44][45][46]. Nevertheless, decreasing the greater NetC w/kg in adults with obesity may be beneficial to increase non-exercise activity thermogenesis (NEAT) [11], and thus, light physical activity energy expenditure (1.6-2.9 metabolic equivalents; METs), which is inversely related to sedentary time [47] and has complementary effects to improve health [48].…”
Section: Discussionmentioning
confidence: 99%
“…Previous study demonstrated that participants with obesity but metabolic healthy (MH) were associated with an increased risk for MI [ 24 ] compared with MH-NW, which suggested an important influence of obesity or overweight on CVDs. A possible mechanism also demonstrated that it is difficult to lose fat when we get fatter, because our body makes more strongly energy compensation that burned during PA [ 41 ]. Therefore, it is importance to maintain healthy weight for decreasing CVDs risk.…”
Section: Discussionmentioning
confidence: 99%